Protrúzia apendixu cez perforacný otvor v cervixe maternice ako zriedkavá komplikácia pri umelom prerusení gravidity - Lakyová, L; Dankovcík, R; Kudlac, M; Mikulová, J; Radonak, J (Ceska gynekologie, 2009)
AIM: Point to an extremly rare complication of a curettage during abortion and follow up surgical treatment of this complicated state. CASE: In the case of 32 years old woman, multipara, was perforated cervix uteri during the abortion curettage and fat tissue of mesentery was aspirated into canulla. Apendix vermiformis was aspirated into cannula with its protrusion through the neck of the womb during repeated revision. Surgeon made appendectomy lege artis after abdomen revision and looking after haemoperitoneum. Because of serious devastation of right fallopian tube, salpingektomy was performed. Perforation of cervix in the lenght of three cm was sutured. Extensive incomplete rupture continuing from perforation gap was sutured from ligamentum sacrouterinum I.dx to fundus uteri. Intact foetus of 5,5 week of gestation was leaved in toto because of the high risk of the womb wall disruption during repeatedly attempted abortion. CONCLUSION: In case of the suspection of the uterus injury a revision and interdisciplinary approach to the solution of complications is necessary.
Keywords: penetrující rány; Adult; těhotenství; Appendix; dospělí; Humans; cervix uteri; lidé; Abortion, Induced; apendektomie; Female; kyretáž; Wounds, Penetrating; Curettage; Appendectomy; ženské pohlaví; Pregnancy; apendix; Cervix Uteri; indukovaný potrat